PERBANDINGAN METODE APLIKASI JAMUR ENTOMOPATOGEN BEAUVERIA BASSIANA UNTUK PENGENDALIAN CYLAS FORMICARIUS (COLEOPTERA: CURCULIONIDAE) - Prayogo, Yusmani (Universitas Lampung, 2017)
Comparing application methods of entomopathogenic fungus Beauveria bassiana to control Cylas formicarius (Coleoptera: Curculionidae). Cylas formicarius is a major pest of sweet potatoes. The tuber damage caused by C. formicarius reaches 100%. The research objective was to compare application methods of entomopathogenic fungi Beauveria bassiana to control C. formicarius. The research was conducted at the entomology screen house of Indonesian Legume and Tuber Crops Research Institute (ILETRI) at Malang, East Java, from January to September 2013. The treatment consisted of 12 application methods, each was repeated three times. The results showed that application of B. bassiana into the planting pit, soaking the sweet potato cuttings into the conidial suspension of B. bassiana for 30 minutes before planting, followed by spray application with two week interval (2 to 12 weeks after planting, WAP) or P4 was effective in suppressing C. formicarius population and tuber damage. Tuber weight obtained from P4 treatment was 1.4 kg plant-1, while from the chemical insecticide was only 1.1 kg plant-1. Tuber damage from P4 treatment was lower ( 5%) than that from chemical insecticide treatment (42%). Therefore, application of B. bassiana conidial suspension in the planting pit, continued by soaking the sweet potato cuttinginto the B. bassiana conidial suspension for 30 minutes before planting, and followed by spray applications of B. bassiana conidial suspension at two-week intervals ( 2-12 WAP) or P4 method can be recommended to control C. formicarius.